A comparison of microhardness of indirect composite restorative materials Estudo comparativo da microdureza de materiais resinosos indiretos - Carolina Baptista Miranda; Clóvis Pagani; Marco Cícero Bottino; Ana Raquel Benetti (University of São Paulo, 2003)
The purpose of this study was to compare the microhardness of four indirect composite resins. Forty cylindrical samples were prepared according to the manufacturer's recommendations using a Teflon mold. Ten specimens were produced from each tested material, constituting four groups (n=10) as follows: G1 - Artglass; G2 - Sinfony; G3 - Solidex; G4 - Targis. Microhardness was determined by the Vickers indentation technique with a load of 300g for 10 seconds. Four indentations were made on each sample, determining the mean microhardness values for each specimen. Descriptive statistics data for the experimental conditions were: G1 - Artglass (mean ±standard deviation: 55.26 ± 1.15HVN; median: 52.6); G2 - Sinfony (31.22 ± 0.65HVN; 31.30); G3 - Solidex (52.25 ± 1.55HVN; 52.60); G4 - Targis (72.14 ± 2.82HVN; 73.30). An exploratory data analysis was performed to determine the most appropriate statistical test through: (I) Levene's for homogeneity of variances; (II) ANOVA on ranks (Kruskal-Wallis); (III) Dunn's multiple comparison test (0.05). Targis presented the highest microhardness values while Sinfony presented the lowest. Artglass and Solidex were found as intermediate materials. These results indicate that distinct mechanical properties may be observed at specific materials. The composition of each material as well as variations on polymerization methods are possibly responsibles for the difference found in microhardness. Therefore, indirect composite resin materials that guarantee both good esthetics and adequate mechanical properties may be considered as substitutes of natural teeth. O objetivo deste estudo foi comparar a microdureza de 4 resinas compostas indiretas. Quarenta amostras cilíndricas foram obtidas com o auxílio de uma matriz de teflon, seguindo-se as recomendações dos fabricantes. Foram obtidas 10 amostras para cada material testado, contituindo-se 4 grupos (n=10) como se segue: G1-Artglass; G2-Sinfony; G3-Solidex; G4-Targis. A microdureza foi determinada pela técnica da indentação Vickers com uma carga de 300g por 10 segundos. Quatro indentações foram realizadas em cada amostra, obtendo-se um valor médio. Os dados da análise estatística descritiva para cada condição experimental foram: G1-Artglass (média ± desvio padrão:55,26 ± 1,15HVN; mediana: 52,6); G2- Sinfony (31,22 ± 0,65HVN; 31,30); G3- Solidex (52,25 ± 1,55HVN; 52,60); G4- Targis (72,14 ± 2,82HVN; 73,30). Uma análise exploratória dos dados foi realizada para determinar o teste estatístico mais apropriado: (I) Teste de Levene para variâncias homogêneas; (II) Teste de ANOVA (Kruskal-Wallis); (III) Teste de comparação múltipla de Dunn. O Targis apresentou os maiores valores de microdureza, enquanto que o Sinfony apresentou os menores valores. O Artglass e o Solidex se comportaram como materiais intermediários. Estes resultados indicaram que propriedades mecânicas distintas podem ser observadas nos materiais. A composição de cada material, bem como as variações nos métodos de polimerização são possivelmente responsáveis pelas diferenças observadas na microdureza. Portanto, materiais resinosos indiretos que garantam estética e propriedades mecânicas satisfatórias podem ser considerados como substitutos dos dentes naturais.